PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN KONSUMEN DALAM MEMILIH TAKSI DI SURABAYA - Gracia, Yudith; Andayani, Sri; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2015)
Consumer behavior is a process through which a person in finding, buying, using, evaluating, and acting after consumption of a product, service or idea that is expected to meet his needs. The study aims to determine the effect of service quality which consists of five dimensions, namely tangibles, reliability, responsiveness, assurance and empathy towards consumer decision in choosing a taxi, especially Blue Bird taxi. By looking at the existing problems, the author formulates the problem as follows: What are the factors of service consisting of tangibles, reliability, responsiveness, assurance and empathy will influence the consumer's decision in choosing a taxi. This research is a quantitative research. Quantitative research is the study of data using a formula - a formula which statistics are irrelevant to the issue. Quantitative data were analyzed using statistical calculations with SPSS. From the research results can be seen that the tangibles, reliability, responsiveness, assurance, empathy. simultaneously influence the decision chose Blue Bird taxi. Partially dimensions of tangibles and empathy positive influence on decision-making. Based on the research results and conclusions can be put forward suggestions - suggestions that could be considered in this study is increase the operational systems as well as maintain services until now executed.  Keywords : are the factors of service consisting of tangibles, reliability, responsiveness, assurance and empathy will influence the consumer's decision